On controllability problems for the wave equation on a half-plane - Fardigola, L.V. (Журнал математической физики, анализа, геометрии, 2005)
Necessary and sufficient conditions for null-controllability and approximate null-controllability are obtained for the wave equation on a half-plane. Controls solving these problems are found explicitly. Moreover bang-bang controls solving the approximate null-controllability problem are constructed with the aid of the Markov power moment problem.